Effect of Co－Opted Board on Audit Fees - 김채현; 이은서; 이준엽 (국제회계연구, 2020)
In this study, we examine the effect of co－opted board on audit fees (as a proxy for audit quality), wherein the board comprises directors who are appointed after the CEO assumes office. We use two measures developed by Coles et al.(2014) to calculate the co－opted board. First, we use CO－OPTION, which is the proportion of the board size comprising the co－opted board. Second, we use TW CO－OPTION, which is the sum of co－opted directors’ tenure divided by the sum of all directors’ tenure. Using a sample of 9,592 firm－year observations in the United States for the period 2000 to 2013, we find that having a high proportion of co－opted board members leads to a decrease in audit quality. This is reflected in the negative relationship between co－opted board and audit fees. This evidence is consistent with the notion that board composition and the effectiveness of board monitoring play significant roles in determining audit fees. Overall, our results are consistent with those of prior studies that co－opted board imposes weak monitoring. In addition, our study contributes to the auditing literature by showing how board composition and monitoring effectiveness influence audit fees.
Keywords: Audit Fees; Audit Quality; Co－Opted Board; 감사보수; 감사품질; 코옵티드 이사